Amino acid sequence identification of goji berry cyclic peptides and anticervical carcinoma activity detection. (6th May 2021) - Ji, Hongxia; Ma, Junxia; Guo, Lianjun; Huang, Yongmei; Wang, Weihong; Sun, Xiuyan; Sun, Rongchun
Abstract : The goji berry is widely used as tonics; however, the antihuman cervical carcinoma effect and underlying mechanism of goji berry peptide remain to be elucidated. The cyclic peptides are appealing targets in antitumor agent development, and in current study, three novel goji berry cyclic peptides (GCPs) were isolated and amino acid sequence identified. Among them, GCP‐1 (Cycle‐(Trp‐Glu‐His‐Thr)) inhibited proliferation and induced human cervical cancer (HeLa) cells apoptosis and blocked the HeLa cells in G0/G1 phase significantly. Furthermore, the GCP‐1 also inhibited the cervical carcinoma growth in vivo. Moreover, GCP‐1 suppressed the cyclin expression and activated the caspase cascade and poly(ADP‐ribose) polymerase. Of note, GCP‐1 may be a promising novel inhibitor of human cervical cancer. Abstract : The goji berry cyclic peptide‐1 (Cycle‐(Trp‐Glu‐His‐Thr)) induced the cancer cell apoptosis through the cyclin expression inhibition accompanied with the caspase activation. Highlights: Three novel goji berry cyclic peptides (GCPs) were amino acid sequences identified, and antiproliferative activity was evaluated in three cervical cancer cell lines (C33A, SiHa, and HeLa) in vitro. GCP‐1 showed the most antiproliferative activity against HeLa cells with an IC50 of 80.2 ± 7.93 μM (48 h). GCP‐1 induced the HeLa cell apoptosis and blocked the HeLa cells in G0/G1 phase. GCP‐1 suppressed the cyclin expression accompanied with the activation of the caspase cascade.